Features of Variable Number of Tandem Repeats in Yersinia pestis and the Development of a Hierarchical Genotyping Scheme. - Yanjun Li (PLoS ONE, 2013)
Variable number of tandem repeats (VNTRs) that are widely distributed in the genome of Yersinia pestis proved to be useful markers for the genotyping and source-tracing of this notorious pathogen. In this study, we probed into the features of VNTRs in the Y. pestis genome and developed a simple hierarchical genotyping system based on optimized VNTR loci.Capillary electrophoresis was used in this study for multi-locus VNTR analysis (MLVA) in 956 Y. pestis strains. The general features and genetic diversities of 88 VNTR loci in Y. pestis were analyzed with BioNumerics, and a "14+12" loci-based hierarchical genotyping system, which is compatible with single nucleotide polymorphism-based phylogenic analysis, was established.Appropriate selection of target loci reduces the impact of homoplasies caused by the rapid mutation rates of VNTR loci. The optimized "14+12" loci are highly discriminative in genotyping and source-tracing Y. pestis for molecular epidemiological or microbial forensic investigations with less time and lower cost. An MLVA genotyping datasets of representative strains will improve future research on the source-tracing and microevolution of Y. pestis.